Design, synthesis, and application in OFET of a small molecule based on π-expanded fused diketopyrrolopyrrole - Li, Jianhui; Ji, Zhuoting; He, Aihua; Zhang, Haichang (Frontiers in Chemistry, 2023)
Diketopyrrolopyrrole (DPP) and its derivatives, as the electron deficient units, are widely used as the building blocks in organic field-effect transistors, which obtained a high performance. However, further modification the DPP structure is crucial for the further development of organic semiconductors. In this work, a (FDPP) is synthesized and characterized. The results shows that the FDPP exhibited not only good planar core structure with a good conjugation system, but also with a strong aggregation in the solid state. Aa a consequence, the FDPP present a p-type behavior with a hole mobility 9.7×10-3 cm2 V−1 s−1. This study suggested FDPP is a promising electron deficient units to high performance semiconductors.